2008
DOI: 10.1080/14756360701747334
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase inhibition by novel fatty acid ester fromAnnona squamosaseeds

Abstract: Studies on the seeds of Annona squamosa yielded a novel lipoxygenase inhibitor fatty acid ester, (þ ) -annonlipoxy (1). Compound 1 was screened for its enzyme inhibitory activity against lipoxygenase (E.C.1.14.18.1), exhibiting activity with IC 50 69.05^5.06 mm. Baicalein (IC 50 22.6^0.5 mm) was used as a positive control. Crude extracts of Annona squamosa fruit pulp and seeds were screened for its enzyme inhibitory activity against lipoxygenase and acetylcholinesterase. The crude ethanolic extract of fruit pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…a double doublet at ¼ 3.45 (J 3,2 ¼ 4.50 Hz, J 3,2 ¼ 12.4 Hz) and a broad double doublet at ¼ 5.62 (J 6,7 ¼ 12.5 Hz, J 6,7 ¼ 4.0 Hz), which could be assigned to the hydroxyl bearing C-3 methine and to the vinylic C-6 protons, respectively. The chemical shift and coupling constants of the C-3 methine signal indicated an equatorial () orientation of the OH group (Sultana, 2008). The equatorial orientation () of the hydroxyl group was inferred from the chemical shift and coupling pattern of geminal C-3 proton at ¼ 3.45 (dd, J 3,2 ¼ 4.50 Hz, J 3,2 ¼ 12.40 Hz).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…a double doublet at ¼ 3.45 (J 3,2 ¼ 4.50 Hz, J 3,2 ¼ 12.4 Hz) and a broad double doublet at ¼ 5.62 (J 6,7 ¼ 12.5 Hz, J 6,7 ¼ 4.0 Hz), which could be assigned to the hydroxyl bearing C-3 methine and to the vinylic C-6 protons, respectively. The chemical shift and coupling constants of the C-3 methine signal indicated an equatorial () orientation of the OH group (Sultana, 2008). The equatorial orientation () of the hydroxyl group was inferred from the chemical shift and coupling pattern of geminal C-3 proton at ¼ 3.45 (dd, J 3,2 ¼ 4.50 Hz, J 3,2 ¼ 12.40 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…The C-12 vinylic proton resonating at ¼ 5.10 showed vicinal couplings with the C-11 methylene protons resonating at ¼ 1.52 and 1.62. The Homonuclear Hartmann Hahn spectrum (Atta-urRahman, Sultana, Jahan, & Choudhary, 2005;Fatima & Sultana, 2003a, 2003bSultana, 2008Sultana, , 2009) recorded with mixing delay of 100 ms showed that the C-3 methine proton is coupled with four protons i.e. with the C-1 and C-2 methylenic protons ( ¼ 1.23/1.25 and 1.61/1.81), respectively.…”
mentioning
confidence: 98%
“…The seeds of Annona squamosa yielded a novel lipoxygenase inhibitor fatty acid ester, (+)-annonlipoxy (Sultana 2008). Annonlipoxy exhibited inhibitory activity against lipoxygenase with IC 50 of 69.05 mm.…”
Section: Lipoxygenase Inhibitory Activitymentioning
confidence: 99%
“…From A. squamosa leaves, two main chemical classes were described: steroids and terpenoids (Savithramma et al, 2011). Particularly, acetogenins and benzylisoquinoline alkaloids isolated from this family have received special attention due to their variety and distribution in Annonaceae representatives in distinct stages of development, including A. squamosa (Yogesh, 1994 (Sultana, 2008), anti-HIV activity of diterpenes from A. squamosa (Wu et al, 1996), and anti-herpetic activity of ethanolic (Padmaja et al, 1995) The relation between biological potential of plants and the plant-environment interface is another point of interest in the A. squamosa studies. Seasonality, circadian cycle, ultraviolet radiation, and temperature, can be considered the main environmental factors involved in reducing and increasing the production rate of secondary metabolites (Taiz and Zeiger, 2008) since A. squamosa seems to show a greater control of transpiration through stomata closure in water deficit situation (Endres, 2007).…”
Section: Review Of Literaturementioning
confidence: 99%